3D Scanning of Workpieces with Cooperative Industrial Robot Arms - Wagner, Maximilian; Heß, Peter; Reitelshöfer, Sebastian; Franke, Jörg (Proceedings of ISR 2016: 47st International Symposium on Robotics, 2016)
This paper describes the realization of a cooperative scanning approach by two industrial robot arms. The basic idea is the distribution of the movements on two robots by one robot handling the sensor and the other one handling the workpiece. Through this approach reachability is improved. In addition, the reference between the workpiece and the grasping robot is included in the scan model. Thus, the resulting model can be used well for subsequent workpiece related machining processes.

3D-Sensorsystem für den kollisionsfreien Betrieb flexibler Strahlentherapiegeräte - Buschhaus, Arnd; Franke, Jörg; Reitelshöfer, Sebastian; Ziegler, Christian; Röttenbacher, Maren (Internationales Forum Mechatronik 2013, 2013)
Ein bedeutendes Mittel zur Behandlung von Tumoren stellt ionisierende Strahlung dar. Neben der Verwendung einer geeigneten Strahlquelle kommt dabei vor allem der Bestrahlungsdosis zur Tumorbehandlung während der Therapieablaufs eine bedeutende Rolle zu. Ziel dieser Behandlungsmethoden ist es, die Belastung des umliegenden Gewebes zu reduzieren und die zeitliche Dauer möglichst kurz zu gestalten. Moderne Therapiegeräte ermöglichen hierzu eine Anpassung der Bestrahlungsrichtung bezüglich des Tumors. Der Strahlenaustritt am Gerät wird dabei auf einer kreisförmigen Bahn um den Tumor bewegt, der sich im Isozentrum der Bestrahlung befindet. Zur flexiblen Behandlung von Tumoren besteht zunehmend die Forderung nach einer Erhöhung der kinematischen Freiheitsgrade des bestrahlenden Gerätes. Einen wesentlichen Einfluss auf die Therapiedauer hat derzeit die notwendige geringe Geschwindigkeit der Kinematik, mit welcher diese zwischen den verschiedenen Bestrahlpositionen bewegt wird. Eine geringe Geschwindigkeit ist erforderlich, um Kollisionen des Patienten mit der Kinematik zu vermeiden und Verletzungen zu verhindern. Aus dieser Forderung ergibt sich ein ungünstiges Verhältnis von den Positionierzeiten des Gerätes zu den Bestrahlzeiten. Dies führt durch die längere Therapiedauer zu einer zusätzlichen Belastung für den Patienten und zu einer schlechteren Auslastung der investitionsintensiven Therapiegeräte. Durch eine zuverlässige Detektion und Positionsbestimmung des Patienten während der Behandlung und das Ableiten geeigneter Reaktionsstrategien ist es möglich die zulässigen Geschwindigkeiten der Therapiegerätekinematik zu erhöhen und somit die Nebenzeiten signifikant zu reduzieren. Um dies zu ermöglichen ist jedoch eine robuste Erkennung des Patienten und potentieller Kollisionen notwendig. In der Medizintechnik und auch der Strahlentherapie werden mittlerweile zunehmend 3D-Kamerasysteme verwendet, die bei der hochgenauen Patientenpositionierung oder der Atemverfolgung eingesetzt werden. Diese Kamerasysteme qualifizieren sich ebenfalls zur behandlungsbegleitenden überwachung des Patienten um Bewegungen zu erkennen. Hierzu ist jedoch eine robuste Verarbeitung der Kameradaten wesentlich. So müssen anfangs fehlerhafte Bildinformationen durch eine geeignete Filterung eliminiert werden. Eine sich anschließende Erkennung des Patienten muss im Weiteren mehreren Anforderungen genügen: So sind Patienten unterschiedlicher Physiognomie zu erkennen, die Lage des Patienten zur Kamera ist per se nicht bekannt und die Position der Patientenliege ist variabel. Die Patientenerkennung wird über einen Algorithmus realisiert, der die räumlichen Lageinformationen der 3D-Kamera verwendet und über den zusammenhängende Regionen bestimmt werden. Die dem Patienten zugewiesenen Bildpunkte werden im Anschluss binärisiert und im Nachgang die Kanten des Binärbildes bereinigt sowie isolierte Bildbereiche beseitigt. Anschließend wird aus den Bildinformationen ein Skelett des Patienten extrahiert. Diese Körperstruktur wird im Weiteren durch Gelenke erweitert, um z. B. eine Unterscheidung der Gliedmaßen zu ermöglichen und deren Winkelstellungen zu ermitteln. Unter Zuhilfenahme dieser Informationen werden im Nachgang Hüllkörper zur Beschreibung des Patienten erzeugt. Basierend auf einem Bestrahlungsplan werden bei der Behandlung die Stellungen des Therapiegeräts und der Kinematik sowie die optimalen Bahntrajektorien zwischen den Bestrahlpositionen generiert. Während der Durchführung der Bewegungsprogramme wird die aktuelle Stellung des Strahlentherapiegeräts auf Kollisionen mit dem Patienten überprüft. Diese erfolgt über eine Durchdringungsanalyse der Hüllkörperrepräsentation des Patienten und einer geometrischen Repräsentation der Kinematik und des Strahlentherapiegeräts. Die zuverlässige Erkennung des Patienten bei den üblichen Körperhaltungen durch die dargestellten Bildverarbeitungsroutinen konnte im Rahmen der Arbeiten experimentell nachgewiesen werden. Potentielle Gefahrensituationen wurden zuverlässig vom Softwaresystem erkannt und resultieren in einem Stopp der Kinematik.
Keywords: - Robotik - 3D Bildverarbeitung - Strahlentherapie - Kollisionsanalyse - Regelung; 3D-Kameras; B|Mech; Industrieroboter-Assistenzsystem; PMD-Kamera; Roboter

Accelerated aerosol-jet-printing of stretchable rGO-electrodes for stacked dielectric elastomers by using a new hybrid atomizer - Reitelshöfer, Sebastian; Martin, Sina; Nendel, Florian; Schäfer, Thomas; Pham, Duc Huy Hoang; Franke, Jörg (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
The efficient manufacturing of dielectric layers and electrodes for dielectric elastomers is challenging especially for stacked configurations. In an earlier publication we describe a contactless programmable manufacturing approach for aerosol-jet-printing stacked silicone and reduced graphene oxide (rGO)-layers in one process device. One limitation of the setup presented there is the long production time of e.g. 45 minutes for a 1 cm2 electrode with a sheet resistance of 1 Mω. This contradicts the goal of printing numerous layers for stacked systems and is related to the usage of an ultrasonic atomizer. Therefore we present a new hybrid atomizer, which significantly lowers the printing times of rGO-electrodes. This hybrid atomizer again uses an ultrasonic aerosol generation system. Hence, particle-inks without chemical stabilizers that would affect the curing process of printed adjacent silicone structures, can still be used in the system over hours without agglomeration. In addition, a pneumatic aerosol generation is integrated with the new hybrid atomizer. The combined material output of the pneumatic and the ultrasonic approach allows for the printing of rGO-electrodes in two minutes or less with characteristics comparable to those described above. Furthermore, a light-heating-system is integrated into the printing system which enables the fast evaporation of the solvents independently of the height of the previously stacked layers. For this new system, several printing strategies are evaluated by comparing different programmed trajectories of the print head. Printed rGO-electrodes with thicknesses from 3-20 μm and values for the sheet resistance from 1 MOhm to 200 kOhm are characterized regarding their ability to bear a maximal deformation up to 100 % and repeated cyclic stretching up to 25 %.
CRIS-Team Scopus Importer:2020-06-05
Keywords: aerosol-jet-printing; hybrid atomizer; rGO-electrodes; stacked dielectric elastomers

Accuracy Analysis and Improvement for Cooperative Industrial Robots - Buschhaus, Arnd; Wagner, Maximilian; Franke, Jörg; Reitelshöfer, Sebastian; Heß, Peter (Proceedings of the 14th International Conference on Informatics in Control, Automation and Robotics, 2017)

A Concept of Emotion-Driven Human-Robot-Inter-Action for Nursing Care Scenarios - Wittenberg, Thomas; Ernst, Andreas; Hauenstein, Thomas; Merz, Nina; Sassen, Sascha; André, Elisabeth; Lu, Shuang; Pest, Christian; Hutschenreiter, Saskia; Berger, Julia; Franke, Jörg; Reitelshöfer, Sebastian; et al. (2024 2nd International Conference on Integrated Systems in Medical Technologies (ISMT), 2024)
'Social robotics’ is a fairly recent field of robotics addressing questions of how mobile robotic platforms must be extended with sensors and data analysis possibilities, enabling them to recognize and interpret the emotional state of their human counterparts and the current situational context to react in an adequate manner. One key application scenario for social robots is in the field of nursing homes and elderly residents. This implicates that social robots must be able to interact with diverse types of roles, ranging from the elderly home inhabitants via relatives and guests to professional health care providers. In order to communicate adequately with humans in a social manner, the interaction strategies must include the information about the emotional states of humans. In this contribution, we propose a concept of an emotion-driven human-robot-interaction scheme, where possible perceived emotional expressions (such as ‘happy’, ‘surprised’ or ‘sad’) are used to trigger corresponding reaction strategies from a repository, which can then be used to react and stabilize the situation. Using the scenario of nursing care as an example, all necessary technical components of social robots are described, and possible dialogues between nursing home residents and robot are simulated with a large language model, whose prompts are enriched by additional information about the possible detected emotional states of the resident

Additiv gefertigte Handprothese - Yoo, In Seong; Reitelshöfer, Sebastian; Franke, Jörg (Technische Unterstützungssysteme, 2015)
Keywords: Additive Manufacturing; B|Mech; Prothetik

Aerosol jet printing and lightweight power electronics for dielectric elastomer actuators - Landgraf, Maximilian; Hedges, Martin; Reitelshöfer, Sebastian; Franke, Jörg (3rd International Electric Drives Production Conference (EDPC), 2013)
Dielectric elastomer actuators have been subject of researches in materials science since almost two decades. The synonymous denotation “artificial muscles” emphasizes the potential capability of those actuators, whereat the skeletal muscles of mammals, which are the biological archetypes, even are exceeded pertaining energy density and efficiency. These new kind of actuators depicts promising actuators for the development of a new generation of robotic solutions, such as inherently safe systems for human robot cooperation, highly dynamical, mobile and energy autarkic kinematics or even prosthetics. Since there are several challenges to be handled, like the high supply voltage, no automated manufacturing process for multilayered dielectric elastomer actuators is available and thus no actuators systems based on dielectric elastomer actuators for complex robot kinematics or commercial products. Now the Aerosol Jet Printing process seems suitable for an automated manufacturing process by printing such actuators and is investigated within the framework of the Bavarian biomimetic initiative “bionicum-forschung”. With this additive process stacked actuators are printed, where insulating and conducting layers are alternating and the automated manufacturing of stacked actuators with thousands of layers seems possible in the long term. With the new built actuators, new mobile and autarkic platforms in the range of a capuchin will be designed. Therefore lightweight power electronics are necessary, which investigation represents the second main research task within the project. Here only one high-mass central power supply is able to individually operate each of the artificial muscles on the platform with a pulse width modulated high voltage signal. Thus each actuator does not need its own supply. The presented project aims with the development of a mobile and autarkic platform the improvement of actual robot platforms regarding to dynamical int- ractions with the environment, like jumping, and the progress of the actual state of the art of robotics.
Keywords: aerosols; biomimetics; electroactive polymer actuators; mobile robots; power electronics; robot kinematics; Bavarian biomimetic initiative; additive process stacked actuators; aerosol jet printing process; artificial muscles; autarkic platforms; automated manufacturing process; biological archetypes; bionicum-forschung; capuchin; complex robot kinematics; conducting layers; energy density; high-mass central power supply; human robot cooperation; insulating layers; lightweight power electronics; mammals; mobile platforms; multilayered dielectric elastomer actuators; pulse width modulated high voltage signal; robot platforms; robotic solutions; skeletal muscles; Actuators; Aerosols; Electrodes; Materials; Printing; Pulse width modulation; Switches; aerosol jet printing; artificial muscles; dielectric elastomer actuators; electroactive polymers; high voltage pulse width modulation; lightweight actuators; stacked actuators

Aerosol Jet Printing and Lightweight Power Electronics for Dielectric Elastomer Actuators - Landgraf, Maximilian; Hedges, Martin; Reitelshöfer, Sebastian; Franke, Jörg (Proceedings of the 3rd International Electric Drives Production Conference (EDPC), 2013)

Aerosol-Jet-Printing silicone layers and electrodes for stacked dielectric elastomer actuators in one processing device - Reitelshöfer, Sebastian; Göttler, Michael; Schmidt, Philip; Treffer, Philipp; Landgraf, Maximilian; Franke, Jörg (SPIE Smart Structures and Materials + Nondestructive Evaluation and Health Monitoring, 2016)
In this contribution we present recent findings of our efforts to qualify the so called Aerosol-Jet-Printing process as an additive manufacturing approach for stacked dielectric elastomer actuators (DEA). With the presented system we are able to print the two essential structural elements dielectric layer and electrode in one machine. The system is capable of generating RTV-2 silicone layers made of Wacker Elastosil P 7670. Therefore, two aerosol streams of both precursor components A and B are generated in parallel and mixed in one printing nozzle that is attached to a 4-axis kinematic. At maximum speed the printing of one circular Elastosil layer with a calculated thickness of 10 μm and a diameter of 1 cm takes 12 seconds while the process keeps stable for 4.5 hours allowing a quite high overall material output and the generation of numerous silicone layers. By adding a second printing nozzle and the infrastructure to generate a third aerosol, the system is also capable of printing inks with conductive particles in parallel to the silicone. We have printed a reduced graphene oxide (rGO) ink prepared in our lab to generate electrodes on VHB 4905, Elastosil foils and finally on Aerosol-Jet-Printed Elastosil layers. With rGO ink printed on Elastosil foil, layers with a 4-point measured sheet resistance as low as 4 kΩ can be realized leaving room for improving the electrode printing time, which at the moment is not as good as the quite good time-frame for printing the silicone layers. Up to now we have used the system to print a fully functional two-layer stacked DEA to demonstrate the principle of continuously 3D printing actuators.

An autonomous robotic system for intralogistics assisted by distributed smart camera network for navigation - Zhang, Xu; Scholz, Michael; Reitelshöfer, Sebastian; Franke, Jörg (2018 IEEE 14TH INTERNATIONAL CONFERENCE ON AUTOMATION SCIENCE AND ENGINEERING (CASE), 2018)
CRIS-Team WoS Importer:2019-03-26

A new production process for soft actuators and sensors based on dielectric elastomers intended for safe human robot interaction - Reitelshöfer, Sebastian; Landgraf, Maximilian; Gräf, Daniel; Bugert, Larissa; Franke, Jörg (2015 IEEE/SICE International Symposium on System Integration (SII), 2015)
Dielectric elastomers are the subject of intense research in material science. A large number of publications describe artificial muscles based on dielectric elastomer actuators as a promising alternative for an energy efficient, lightweight and flexible actuation architecture. Dielectric elastomer actuators could improve and extend the capabilities of robots in terms of soft kinematics for the direct physical interaction between humans and robots. They could also improve the dynamical performance and the eligibility for energy autarkic operation of robotic systems. Another field of application are dielectric elastomer sensors that can bear and detect large deformation. However, up to now dielectric elastomer actuators and sensors are not available on a large scale with reproducible characteristics. The focus of this contribution lies on a new automated production process using Aerosol-Jet-Printing for dielectric elastomer actuators and sensors with very favorable characteristics resulting from the additive manufacturing aiming at an improved availability of such sensors and actuators.
Keywords: deformation; electroactive polymer actuators; human-robot interaction; industrial robots; rapid prototyping (industrial); three-dimensional printing; additive manufacturing; aerosol-jet-printing; artificial muscles; automated production process; deformation detection; dielectric elastomer actuators; dielectric elastomer sensors; energy autarkic operation; energy efficient lightweight flexible actuation architecture; human-robot physical interaction; robot kinematics; robotic systems; soft actuators; soft sensors; Actuators; Dielectrics; Printing; Sensor phenomena and characterization; Service robots

A Novel Concept for Unidirectional Communication With an Active Implant Based on Deliberately Produced Human Body Signals. - Benke, Elisabeth; Preis, Alexander; Schulz, Alisa; Reitelshöfer, Sebastian; Franke, Jörg (Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2022)
A new patient-friendly and discrete approach to build a unidirectional communication path with active implants based on deliberately produced human body signals is presented. The application for which this approach is intended is an artificial urinary sphincter implant, the closure mechanism of which is wirelessly actuated in the event of micturition need. Conventional implant communication methods can be associated with limitations regarding technological implementation and usability, and are used by medical professionals only. In order to enable patients to discretely and directly communicate with their implant without the need for an external handheld device, the feasibility of a communication approach based on manually applied 'knocking' signals on abdominal tissue is examined in the presented work. A gelatin-based phantom model is used to mimic vibro-acoustic properties of human soft tissue in vitro. A piezoelectric element and an electret microphone are applied as sensors for signal detection at the implantation site and are investigated with respect to their suitability for the intended application. Clinical Relevance- The presented implant communication method can contribute to urinary incontinence therapy by enabling patients to discretely and user-friendly actuate their artificial sphincter implant and can provide a basis for future research into new implant communication technologies.
Keywords: Urinary incontinence; medical implant; implant communication

Anwendungsbeispiel: Robotergestützte Systeme in der Medizin - Reitelshöfer, Sebastian (Handbuch Mensch-Roboter-Kollaboration, 2019)

A robot motion planner for 6-DOF industrial robots based on the cell decomposition of the workspace - Ramer, Christina; Reitelshöfer, Sebastian; Franke, Jörg (IEEE ISR 2013, 2013)
This paper describes an autonomous robot motion planner for 6-DOF industrial robots based on the approximate cell decomposition of the workspace. Known obstacles lead to a hierarchical decomposition up to a predefined degree of the start cell which contains the whole robot workspace. A connectivity tree is searched for the shortest path from the start to the goal position for the Tool Center Point (TCP) of the robot. Center points and points between adjacent cells are used as interpolation points for the robot's path. All possible configurations are calculated for these points and checked for absence of collisions and compliance with kinematic constraints. Subsequently paths between possible configurations of interpolation points are checked for feasibility. If points cannot be reached artificial obstacles are constructed and the work space model is updated.
Keywords: cellular manufacturing; collision avoidance; industrial robots; interpolation; mobile robots; robot kinematics; trees (mathematics); 6-DOF industrial robots; TCP; adjacent cells; autonomous collision free path planning; autonomous robot motion planner; connectivity tree; interpolation points; kinematic constraints; path planning problem; tool center point; work space model; workspace cell decomposition; Automation; EMTP; Gold; Mars; Planning; Service robots; 6-DOF industrial robot; cell decomposition method; operational space planner; robot motion planner

Artificial muscles, made of dielectric elastomer actuators - a promising solution for inherently compliant future robots - Yoo, In Seong; Reitelshöfer, Sebastian; Landgraf, Maximilian; Franke, Jörg (Springer Berlin Heidelberg, 2015)
The cutting-edge robotic technology can deal with a lot of complex tasks. However, one of the most challenging technological obstacles in robotics is the development of soft actuators. Remaining challenges in the field of drive technology can be overcome with innovative actuator concepts, for example dielectric elastomer actuators (DEAs). DEAs show numerous advantages in comparison to prevailing robotic actuators that are based on geared servomotors: They are formflexible, inherently compliant, can store and recuperate kinetic energy, feature high power-to-weight ratio and high energy density that is comparable to human skeletal muscles, and finally can be designed to perform natural motion patterns other than rotation. In this article, after a review on disadvantages of state-of-art robotic drives, which are stimulus for a research on the promising drive solution, benefits of DEAs will be presented with regard to the possibility of applications in soft robotics. Finally, the article will conclude with a brief report on the ongoing research effort at the Institute for Factory Automation and Production Systems (FAPS) with two major foci – the development of an automated manufacturing process for stacked DEAs and a lightweight control hardware.
CRIS-Team Scopus Importer:2023-03-07

Artificial muscles, made of dielectric elastomer actuators - A promising solution for inherently compliant future robots - Yoo, In Seong; Reitelshöfer, Sebastian; Landgraf, Maximilian; Franke, Jörg (Soft Robotics, 2015)
Keywords: artificial muscles; B|Mech; Künstliche Muskeln; Soft Robotics

Augmented Virtuality Input Demonstration Refinement Improving Hybrid Manipulation Learning for Bin Picking - Blank, Andreas; Zikeli, Lukas; Reitelshöfer, Sebastian; Karlidag, Engin; Franke, Jörg (Lecture Notes in Mechanical Engineering, 2023)
Beyond conventional automated tasks, autonomous robot capabilities aside human cognitive skills are gaining importance in industrial applications. Although machine learning is a major enabler of autonomous robots, system adaptation remains challenging and time-consuming. The objective of this research work is to propose and evaluate an augmented virtuality-based input demonstration refinement method improving hybrid manipulation learning for industrial bin picking. To this end, deep reinforcement and imitation learning are combined to shorten required adaptation timespans to new components and changing scenarios. The method covers initial learning and dataset tuning during ramp-up as well as fault intervention and dataset refinement. For evaluation standard industrial components and systems serve within a real-world experimental bin picking setup utilizing an articulated robot. As part of the quantitative evaluation, the method is benchmarked against conventional learning methods. As a result, required annotation efforts for successful object grasping are reduced. Thereby, final grasping success rates are increased. Implementation samples are available on: https://github.com/FAU-FAPS/hybrid_manipulationlearning_unity3dros
CRIS-Team Scopus Importer:2022-11-25
Keywords: Bin picking; Human-in-the-loop; Machine learning; Mixed reality

Automated electrical characterization setup for aerosol-jet-printed dielectric elastomer transducers - Martin, Sina; Kaßner, Sebastian; Bruns, Arne; Schärfe, Paul; Reitelshöfer, Sebastian; Franke, Jörg (Online international conference on Electromechanically Active Polymer (EAP) transducers & artificial muscles, 2021)
For the production of stacked and individually shaped dielectric elastomer (DE) transducers, the aerosol-jet-printing had been chosen and further developed at our institute. This printing technology allows the alternating direct deposition of thin layers of either silicone dielectrics or reduced graphene particle electrodes. As the layers are deposited line-wise the surface quality is an issue that has to be considered to obtain constant and predictable electro-mechanical parameters. Typically the characterization of those material systems is performed following the standards for DE testing by Carpi, et al. Based on this established standard we built up our test bench for mechanical and electrical multi-analysis of the printed DE. Furthermore, the setup has been automated to make DE characterization more precise and to facilitate the comparison of a large number of samples in order to create a validation routine to optimize the production process. To allow precise positioning of the specimen the four-axis have been motorized and the program interfaces are used to align the generated information with other measurable parameters such as environmental conditions or timestamps.<br
Keywords: Dielectric elastomer transducers; automated measurement; testing standards; system charcterization

Automated Individualization of Object Detectors for the Semantic Environment Perception of Mobile Robots - Hofmann, Christian; May, Christopher; Ziegler, Patrick; Ghotbiravandi, Iliya; Franke, Jörg; Reitelshöfer, Sebastian (Proceedings of the International Joint Conference on Computer Vision, Imaging and Computer Graphics Theory and Applications, 2025)
Large Language Models (LLMs) and Vision Language Models (VLMs) enable robots to perform complex tasks. However, many of today’s mobile robots cannot carry the computing hardware required to run these models on board. Furthermore, access via communication systems to external computers running these models is often impractical. Therefore, lightweight object detection models are often utilized to enable mobile robots to semantically perceive their environment. In addition, mobile robots are used in different environments, which also change regularly. Thus, an automated adaptation of object detectors would simplify the deployment of mobile robots. In this paper, we present a method for automated environment-specific individualization and adaptation of lightweight object detectors using LLMs and VLMs, which includes the automated identification of relevant object classes. We comprehensively evaluate our method and show its successful application in principle, while also pointing out shortcomings regarding semantic ambiguities and the application of VLMs for pseudo-labeling datasets with bounding box annotations.
CRIS-Team Scopus Importer:2025-04-11
Keywords: Large Language Model; Open Vocabulary Object Detection; Pseudo-Labeling; Vision Language Model

Automated programming of cooperating industrial robots - Wagner, Maximilian; Reitelshöfer, Sebastian; Heß, Peter (ISR/Robotik 2014; 41st International Symposium on Robotics, 2014)
Due to the technological development, products are becoming increasingly complex. In order to implement their sophisticated manufacturing processes, more and more often cooperative industrial robots are used. The challenge in cooperative applications is the complicated programming. Using an automated programming that is done by a generator is a corrective for this. The aim of the project described here is to divide application processes on two industrial robots by one robot holding the tool and the other one the workpiece. The adhesive or sealant application serves as an example for this. The process movements are effectively divided between the two robots in consideration of boundary conditions. To enable programming of such complex tasks for non-experts, an automated program generation with an intuitive programming interface is used.

Automatisierte Pfadgenerierung und Kollisionsüberwachung für Sechsachs-Industrieroboter durch 3D-kameragestützte Umgebungserfassung - Ramer, Christina; Reitelshöfer, Sebastian; Franke, Jörg (Kongress Automation, 2013)

Cable-driven robotic joint for automated hammering Seilrobotergelenk für automatisiertes Hämmern - Walter, Jonas; Nemoto, Takeru; Bachmann, Christian; Gerlich, Matthias; Reitelshöfer, Sebastian; Franke, Jörg (wt Werkstattstechnik - Online, 2022)
Conventional robots are vulnerable to high impact loads due to the configuration of rigid joints and fragile gears. This paper shows that a robotic joint based on a novel topology with three active and three passive cables can cope with impact loads as they occur in machining tasks such as hammering.
Created from Fastlane, Scopus look-up

Challenges in gesture control of robots based on multi-degree of freedom movement recognition with dielectric elastomer sensors - Landgraf, Maximilian; Reitelshöfer, Sebastian; Yoo, In Seong; Franke, Jörg (5th International Conference on Electromechanically Active Polymer & Transducers & Artificial Muscles (EuroEAP), 2016)
Keywords: artificial muscles; Biomechatronik; DEA; EAP; Electromyography (EMG); Robot Control

Combining a collaborative robot and a lightweight Jamming-Gripper to realize an intuitively to use and flexible co-worker - Reitelshöfer, Sebastian; Ramer, Christina; Gräf, Daniel; Matern, Falko; Franke, Jörg (2014 IEEE/SICE International Symposium on System Integration, 2014)
By using collaborative robotic systems, new approaches like programming by demonstration can effectively be realized. As (re)programming of robots thereby gets fast and easy, such systems can facilitate the transition of industrial robots to flexible automation solutions suitable for small companies and small batch sizes. One reason that is preventing the usage of those robots on a broader scale is the fact that for nearly every different work piece a new gripping system has to be designed or at least mechanically adapted. The presented integration of a collaborative robot with a universal Jamming-Gripper broadens the spectrum of parts that can be handled by one robotic system without any mechanical modification.
Keywords: grippers; industrial manipulators; robot programming; collaborative robotic systems; flexible co-worker; gripping system; industrial robots; lightweight jamming-gripper; programming by demonstration; universal jamming-gripper; Educational institutions

Continuous aerosol-jet-printing of silicone layers for dielectric elastomer actuators - Reitelshöfer, Sebastian; Landgraf, Maximilian; Yoo, In Seong; Franke, Jörg (5th International Conference on Electromechanically Active Polymer (EAP) & Artificial Muscles (EuroEAP), 2015)

Cooperative Processing with Multi-Robot Systems - Wagner, Maximilian; Heß, Peter; Reitelshöfer, Sebastian; Franke, Jörg (IEEE/ASME International Conference on Advanced Intelligent Mechatronics, AIM, 2017)
Multi-robot systems are increasingly utilized for cooperative industrial robot applications. In the scope of this work, a novel approach for the division of robot applications between multiple robots by handling the tool and the workpiece at the same time is presented. The approach has been tested successfully with a robot setup with two industrial robot arms. It is shown that the processing time can be reduced and the reachability can be improved by the developed approach. In order to compensate complex programming of the cooperative tasks, an automatic programming is also realized. Thus, the programming time can be significantly reduced.
CRIS-Team Scopus Importer:2023-03-07

Cost-efficient, true silicone printer with variable material spectrum for individualized medical applications - Martin, Sina; Gugel, Lukas; Martin, Thomas; Preis, Alexander; Reitelshöfer, Sebastian; Franke, Jörg (Procedia CIRP, 2021)
Due to their beneficial material properties, silicones have become increasingly important in the healthcare sector. However, common manufacturing techniques like injection molding are limited. Hence, silicones have become more interesting for additive manufacturing, as it is possible to freely shape individualized products in small quantities. We present a syringe printer architecture for personalized manufacturing of medical products that allows a variable mixing ratio for RTV-2 crosslinking silicones and precise dosing. Compared to other printing methods, various commercially available one or two-component silicones with variable part viscosities can be printed in a broad range from 10-3Pas up to 10³ Pas.
Keywords: Additive manufacturing; individualized healthcare; silicone printing; medical grade silicones

Data fusion between a 2D laser profile sensor and a camera - Wagner, Maximilian; Heß, Peter; Reitelshöfer, Sebastian; Franke, Jörg (2015 12th International Conference on Informatics in Control, Automation and Robotics (ICINCO), 2015)
This paper describes a color extension of a 2D laser profile sensor by extracting the corresponding color from a camera image. For these purpose, we developed a routine for an extrinsic calibration between the profile sensor and the camera. Based on the resulting translation and rotation vectors a belonging pixel can be calculated for each profile point. Consequently, the color for each profile point can be extracted from the image. This approach is used to extend the geometric data of a robotic based 3D scanning system by color data.
Keywords: calibration; cameras; geometry; image colour analysis; image fusion; image resolution; image sensors; robot vision; 2D laser profile sensor; camera image; color data; color extension; data fusion; extrinsic calibration; image profile point extraction; robotic based 3D scanning system; rotation vectors; translation vectors; Calibration; Cameras; Image color analysis; Robot kinematics; Robot sensing systems; Three-dimensional displays; 3D Reconstruction; Calibration; Color Extension; Sensor Data Fusion; Workpiece Scanning

Development of a lightweight hardware for controlling multiple dielectric elastomer actuators - Landgraf, Maximilian; Reitelshöfer, Sebastian; Yoo, In Seong; Franke, Jörg (4th International Conference on Electromechanically Active Polymer (EAP) Transducers & Artificial Muscles, 2014)
Keywords: B|Mech

Dielectric elastomer actuators as self-sensing devices: A new method of superimposing actuating and sensing signals - Landgraf, Maximilian; Zorell, Ulrich; Wetzel, Thomas; Reitelshöfer, Sebastian; Yoo, In Seong; Franke, Jörg (SPIE Smart Structures NDE, 2015)
Keywords: dielectric elastomer actuator; dielectric elastomer sensor; self-sensing actuator; superimposition of actuating and sensing signals

Dielectric elastomer actuators - On the way to new actuation-systems driving future assistive, compliant and safe robots and prostheses - Reitelshöfer, Sebastian; Landgraf, Maximilian; Yoo, In Seong; Hörber, Johannes; Ramer, Christina; Ziegler, Christian; Franke, Jörg (5th IEEE RAS/EMBS International Conference on Biomedical Robotics and Biomechatronics, 2014)
For almost 20 years, dielectric elastomer actuators (DEAs) have been the subject of intense research in material science. A large number of publications describe artificial muscles based on DEAs as a promising alternative for an energy efficient, lightweight and flexible actuation architecture. DEAs could improve and extend the capabilities of robotic and prosthetic devices in terms of their dynamical performance and their eligibility for energy autarkic operation. However, up to now DEAs are not available on a large scale with reproducible characteristics nor are they yet usable on a system integration level. In this paper we present recent findings of our ongoing five-year project to qualify DEAs as feasible artificial muscles for usage in compliant robot kinematics and soft prosthetic devices. The focus of this contribution lies on a new automated production process using Aerosol Jet Printing for stacked DEAs with very thin layers for reduced driving voltages and improved mechanical characteristics resulting from the additive manufacturing. Secondly, a new set of lightweight power electronics based on pulse width modulation (PWM) is presented which aims at the improvement of the overall specific power of DEA driven kinematic systems.
Keywords: compliant mechanisms; electroactive polymer actuators; prosthetics; robot kinematics; DEA driven kinematic systems; PWM; actuation systems; additive manufacturing; aerosol jet printing; artificial muscles; assistive robots; automated production process; compliant robot kinematics; dielectric elastomer actuators; lightweight power electronics; pulse width modulation; safe robots; soft prosthetic devices; Biomechatronics; Conferences; Robots

Ein Werkstoff für künstliche Muskeln und weiche Sensoren - Reitelshöfer, Sebastian; Landgraf, Maximilian; Franke, Jörg (2017)

Electrical and mechanical characterization of medical grade silicones as dielectric layers in aerosol jet printed dielectric elastomers - Martin, Sina; Himmler, Marcus; Bruns, Arne; Reitelshöfer, Sebastian; Pham, Duc Huy Hoang; Schubert, Dirk W.; Franke, Jörg (Proceedings Volume 11587, Electroactive Polymer Actuators and Devices (EAPAD) XXIII, 2021)
The name artificial muscles has given dielectric elastomer actuators much attention in the field of medical technology. In healthcare applications, these compliant materials are particularly suitable for soft and lightweight actuators and in addition, they show many advantageous properties such as great extensibility for on-body sensors. However, the lack of industrial scaled production capabilities is still a limiting factor in the transfer of these promising materials into a broad application. To address this issue, we have modified an aerosol jet printer for automated stacking of electrodes and dielectric layers in one process device, which is described in earlier publications. As the performance is mainly dependent on the electrical and mechanical characteristics of the dielectric, a broad material variety is required to face different tasks in healthcare technology. Therefore, different medical grade silicones are investigated in this paper regarding the suitability for aerosol jet printing. In a first step, the printing parameters are derived from rheological testing of the uncured components that are used pure and in mixture with silicone oils to vary the specific Young’s module. Through heat application and dilution, the range for printable materials increases to silicones with initial viscosities up to 8200 mPas. Subsequently aerosol jet printing is used to manufacture stacked silicone dielectrics that are then investigated regarding their mechanical and electrical characteristics for dielectric elastomers. Finally, the collected parameters are compared and an overview of the feasible property combinations is given which can be used as a material guideline for different applications.<br
Keywords: dielectric elastomers; medical grade silicones; mechanical characterization; electrical testing; additive manufacturing; rheological measurement; aerosol jet printing

Gesture Recognition with Sensor Data Fusion of Two Complementary Sensing Methods - Landgraf, Maximilian; Yoo, In Seong; Seßner, Julian; Mooser, Maximilian; Kaufmann, Dominik; Mattejat, David; Reitelshöfer, Sebastian; Franke, Jörg (7th IEEE International Conference on Biomedical Robotics and Biomechatronics (Biorob), 2018)

Herstellungsverfahren gestapelter dielektrischer Elastomeraktoren und Vorbereitung für den Einsatz in mobilen Kinematiken - Landgraf, Maximilian; Reitelshöfer, Sebastian; Franke, Jörg (2013)

Highly Dynamic 2-DOF Cable-Driven Robotic Wrist based on a Novel Topology - Nemoto, Takeru; Walter, Jonas; Bachmann, Christian; Gerlich, Matthias; Reitelshöfer, Sebastian; Franke, Jörg (IEEE Robotics and Automation Letters, 2022)
This paper presents a highly dynamic cable-driven robotic wrist with two degrees of freedom (DOFs). It is based on a novel topology that combines three passive cables for kinematic constraint and the minimal number of active cables for the full control of a movable platform in two rotational DOFs. For a certain geometry of the wrist, the workspace is analyzed using the structure matrix. To control the motion of the wrist, the use of an inertial measurement unit is proposed to directly estimate the orientation and angular velocity, contrarily to the majority of previous cable-driven mechanisms whose control relies on the forward kinematics. Based on the measured data, a standard cascaded controller calculates target torques about two fixed axes of rotation, which are converted into target tensions for the three active cables by the existing closed-form solution. The proposed concept is validated with a hardware prototype. A quasi-static experiment shows that the wrist covers a workspace of up to 55 about both rotation axes. Highly dynamic rotations are demonstrated by step responses with an angular velocity of up to 700/s.<br
Keywords: Wrist; Robots; Torque; Actuators; Topology; Dynamics; Kinematics

High-Precision Visual Servoing for the Neutron Diffractometer STRESS-SPEC at MLZ - Landesberger , Martin; Kedilioglu, Oguz; Wang , Lijiu; Gan , Weimin; Kornmeier , Joana Rebelo; Reitelshöfer, Sebastian; Franke, Jörg; Hofmann , Michael (Sensors, 2024)
With neutron diffraction, the local stress and texture of metallic components can be analyzed non-destructively. For both, highly accurate positioning of the sample is essential, requiring the measurement at the same sample location from different directions. Current sample-positioning systems in neutron diffraction instruments combine XYZ tables and Eulerian cradles to enable the accurate six-degree-of-freedom (6DoF) handling of samples. However, these systems are not flexible enough. The choice of the rotation center and their range of motion are limited. Industrial six-axis robots have the necessary flexibility, but they lack the required absolute accuracy. This paper proposes a visual servoing system consisting of an industrial six-axis robot enhanced with a high-precision multi-camera tracking system. Its goal is to achieve an absolute positioning accuracy of better than (Formula presented.) m. A digital twin integrates various data sources from the instrument and the sample in order to enable a fully automatic measurement procedure. This system is also highly relevant for other kinds of processes that require the accurate and flexible handling of objects and tools, e.g., robotic surgery or industrial printing on 3D surfaces.
CRIS-Team Scopus Importer:2024-05-24
Keywords: automation; computer vision; high accuracy; neutron diffraction; residual stress analysis; robotics; texture analysis; visual servoing

Induction of anisotropic motions in dielectric elastomer actuators by additive manufacturing - Martin, Sina; Riethmüller, J.; Weigand, C.; Reitelshöfer, Sebastian; Franke, Jörg (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
Dielectric elastomer actuators (DEA) exhibit homogeneous driving behavior due to the incompressible material properties of the homogeneous dielectric. This causes the system to expand uniformly in-plane while decreasing its height. In many applications, however, linear actuation is required and the system must be adjusted to operate unidirectionally. For this purpose, different approaches, such as rolling or mechanical stiffening of the actuator, are presented in literature, which aim at adjusting the DEA to work in one direction. In addition, pre-stretching the elastomer film in the required direction can cause the uniaxial motion. Furthermore, there are reports of interpenetrating networks (IPN) forming an anisotropic network that behaves differently depending on the direction. However, these modifications require either external, usually rigid hardware, or additional manufacturing steps that increase the complexity of the process. In the present work, an anisotropic expansion is introduced by our additive manufacturing technique based on aerosol jet printing. By varying the material distribution and the printing of different patterns, the mechanical and electrical properties are changed, resulting in anisotropic driving behavior. In-plane motion is observed with a camera, and the relationship between longitudinal and transverse strain is evaluated using image processing. Systematic design of experiments (DoE) is used to analyze the influencing factors and determine the most promising system design and achievable aspect ratio.
CRIS-Team Scopus Importer:2022-06-24
Keywords: additive manufacturing; anisotropy; asymmetric expansion; Dielectric elastomer actuators; electrode pattern; heterogeneous electrodes

Intraurethral Energy Harvesting from Urine Flow as an approach to power Urologic Implants - Benke, Elisabeth; Stoinski, Robin Thi; Preis, Alexander; Reitelshöfer, Sebastian; Martin, Sina; Franke, Jörg (43rd Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2021)
Active urologic implants, such as bladder stimulators or artificial sphincters, are a widely-used approach for therapy of urinary incontinence. At present these devices are powered by primary batteries or conventional wireless power transferring techniques. As these methods are associated with several limitations, human body energy harvesting can be a promising alternative or complement for power supply. This paper introduces an approach to harvest energy from the urine flow inside the urethra with a mechatronic harvesting system based on a hubless flow turbine. Using a test bench approximating the flow conditions of the lower urinary tract, the feasibility of the harvesting principle is shown in-vitr
Keywords: Energy Harvesting; Implantable Medical Devices

Intuitive Gesture Control of Robots with a Sensor Arm Sleeve Based on Dielectric Elastomer Sensors - Landgraf, Maximilian; Reitelshöfer, Sebastian; Hofmann, Veit; Zimber, Fabian; Yoo, In Seong; Franke, Jörg (6th IEEE RAS & EMBS International Conference on Biomedical Robotics and Biomechatronics (BioRob), 2016)
Keywords: Biomechatronik; Dielectric Elastomer Sensors (DES); Gesture-Based Control; Human-Machine Interface (HMI); Robot Control

Kooperierende Roboter für Montageaufgaben - Reitelshöfer, Sebastian (Handbuch Fügen, Handhaben, Montieren, 2014)

Kostenminimierte, additiv gefertigte Handprothese für den Einsatz in Entwicklungsländern - Yoo, In Seong; Hawelka, Frederik; Reitelshöfer, Sebastian; Franke, Jörg (Erste Transdisziplinäre Konferenz – Technische Unterstützungssysteme, die die Menschen wirklich wollen, 2014)
Keywords: Additive Manufacturing; B|Mech; Prothetik

Künstliche Muskeln auf Basis von dielektrischen Elastomeraktoren (DEA) - Yoo, In Seong; Reitelshöfer, Sebastian; Landgraf, Maximilian; Franke, Jörg (Kongress und Ausstellung Medizin Innovativ – MedTech Pharma 2014, 2014)
Keywords: B|Mech; DEA; Künstliche Muskeln

Lightweight Control Method for Dielectric Elastomer Actuators as Self-Sensing Artificial Muscles - Landgraf, Maximilian; Ollech, Johannes; Klemm, Tobias; Schaude, Janik; Reitelshöfer, Sebastian; Franke, Jörg (2nd IEEE International Conference on Cyborg and Bionic Systems (CBS), 2018)

Mechanical modifications of soft actuators for the use as a dynamic iris implant - Martin, Sina; Schwab, Jürgen; Caballero Lopez, Patricio; Benke, Elisabeth; Reitelshöfer, Sebastian; Franke, Jörg (43rd Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2021)
Aniridia is a condition characterized by defects or absence of the iris. Since the eyes are a central point of attention in the human face, these deformities are often covered with cosmetic implants. However, patients suffer from the static pupil diameter of these implants, resulting in high light sensitivity or inadequate night vision. Therefore, we present a functional iris implant based on dielectric elastomer actuators. These electric drives are characterized by a silent and continuous adaptation as well as a small construction volume and a low heat emission. Since they normally exhibit in-plane uniaxial motion, this displacement must be focused to operate similarly to the iris sphincter. Therefore, we investigated possible mechanical modifications of the setups to generate a directional motion. The results of the study are presented and discussed.Clinical Relevance- The proposed system design enables the functional treatment of aniridia and other accidental iris defects. In addition, the system serves as a basis for later developments of e.g. functional lenses that allow focus adjustment.
Created from Fastlane, Scopus look-up

Minimalinvasives Implantat für die Harninkontinenztherapie - Preis, Alexander; Benke, Elisabeth; Reitelshöfer, Sebastian; Rieker, Ralf (2024)
Der Weg von der Forschungsidee zum zulassungsfähigen Medizinprodukt ist zeit-, kosten- und ressourcenintensiv. Dies zeigt das Beispiel eines Projektes am Lehrstuhl FAPS der Friedrich-Alexander-Universität Erlangen-Nürnberg. Hier arbeitet ein Forscherteam seit einigen Jahren gemeinsam mit medizinischen Partnern an der Entwicklung eines minimalinvasiven Implantats zur Harninkontinenztherapie. Für die Forscher stellt das Vorhaben eine spezielle Anforderung dar, da für wissenschaftliches Arbeiten und eine angestrebte Unternehmensgründung oftmals konträre Wege beschritten werden müssen. Mit der richtigen Unterstützung, strukturellen Voraussetzungen und dem richtigen Mindset aber können beide Ziele erfolgreich vereint werde
Keywords: Harninkontinenztherapie; Forschungstransfer; Start-up; Implantat; Medizinproduktentwicklung

Morphologically intelligent dielectric elastomer sensors based on micro-structured electrodes as resistive strain elements - Martin, Sina; Reitelshöfer, Sebastian; Franke, Jörg (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
Dielectric elastomer sensors (DES) are compliant systems that, allow the detection of geometric changes caused by external forces. However, a simple DES provides only the amplitude of a deformation. In order to fully describe a tensile force vector, it is necessary to characterize it by its length, direction, and origin. Therefore, there are many approaches to improve the information that can be obtained from the sensor, such as arranging DES patterns or modifying the impact of the applied mechanical force by using external components. To improve and parallelize the information provided by the mechanical deformation of the system, we aim to combine the operation principle of structured resistive strain sensors with the capacitive properties of DES. By structuring the electrodes with different patterns and combining two dissimilar electrodes in one setup, it is possible to detect the length and direction of a force vector with one sensing element. To study the patterning and its effect on resistive and capacitive signals, we use an aerosol jet printing technique that allows selective deposition of a conductive ink. The printed lines show a higher resistance increase when forced perpendicular to the pattern and vice versa, which allows to distinguish the direction and the type of applied force. In this study, the influence of printing parameters and signal interpretation for different forces are investigated. The results show that the combination of resistive and capacitive signals allows discrimination between different motions.
CRIS-Team Scopus Importer:2023-10-20
Keywords: aerosol jet printing; Dielectric elastomer sensors; embodied intelligence; morphological intelligence; strain sensors; structured electrodes

Mutter Natur als Vorbild: Bionische Lösungen treiben die Automatisierung an - Landgraf, Maximilian; Reitelshöfer, Sebastian; Franke, Jörg (2013)
Keywords: B|Mech

My new colleague has artificial muscles: a DEA based approach for inherently compliant robotic systems - Yoo, In Seong; Landgraf, Maximilian; Ramer, Christina; Reitelshöfer, Sebastian; Ziegler, Christian; Franke, Jörg (Production Engineering, 2014)
Keywords: Artificial muscles; Compliant actuators; Dielectric elastomer actuators; Electroactive polymers; Human–robot collaboration; Safe robotic systems

Novel Concept for a Mechanical Intraurethral Artificial Urinary Sphincter - Preis, Alexander; Treviranus, Johannes; Benke, Elisabeth; Reitelshöfer, Sebastian; Franke, Jörg (Proceedings of the 15th International Joint Conference on Biomedical Engineering Systems and Technologies - BIODEVICES, 2022)
Stress urinary incontinence is a common pathologic condition in society and an increasing socio-economic challenge. Current artificial urinary sphincters for severe cases have high failure rates, cannot be applied sex-independent and their handling is not intuitive. To address these issues, a novel intraurethral closure system was developed. It works without an external energy supply and consists of an inflatable balloon that presses against the inner contour of a surrounding cylindrical structure implanted in the urethra. Regulation of the closure system is achieved by the interaction of the three main components: the closure balloon, the throttle and the compensating reservoir. The developed closing mechanism seals the bladder at rest and during short peak loads and opens only when the bladder pressure is increased by pressing with the abdominals for a longer period of time for micturition.<br
Keywords: Implant; Urinary Incontinence; Stress Incontinence; Artificial Urinary Sphincter; Intraurethral

Novel measurement setup for dielectric elastomer sensors enabling the detection of multiple load scenarios with integrated adjustment for scalable sensor sizes - Martin, Sina; Schieber, Maximilian; Reitelshöfer, Sebastian; Pham, Duc Huy Hoang; Franke, Jörg (Proc. SPIE 11587, Electroactive Polymer Actuators and Devices (EAPAD) XXIII, 2021)
In healthcare products the proper fit of e.g. orthosis is crucial for its therapeutic success. To monitor movement and pressure, sensors with the ability to adapt their shape to the curvilinear form of the human body as well as a highly dynamic performance during motion are needed. Dielectric elastomer sensors (DES) present most of the required specifications and can be an excellent solution for body-near motion detection. For signal capturing either changes in resistance, capacitance or impedance can be measured. Therefore, different circuit configurations can be used that follow different methods e.g. frequency based or an impedance approach. In this paper, an impedance measurement bridge that enables the detection of stretch and pressure loads with a frequency of 200 Hz is modified. The novel architecture is conceptualized to work with a battery based energy supply and have small enough dimensions to function as a wearable with a wireless communication interface. Furthermore, our former presented additive manufacturing method for dielectric elastomers via aerosol jet printing allows an integrated tuning of the measurement bridge in the process. In addition, to the electrodes of the capacitor one electrode with a defined layer resistance is stacked on top of the DES. Hence, the additional electrode, which makes the architecture scalable for different sensor sizes and shapes, serves as an integrated adjustment of the measurement bridge. The data acquisition of multiple sensors is feasible by time division multiplexing, but is limited in its frequency due to the switching rate of the multiplexer.<br
Keywords: dielectric elastomer sensors; sensing circuit; capacitive; pressure and strain sensors; multiple load; flexible electronics; stretchable sensors; additive manufacturing

On modelling and simulation of dielectric elastomer actuators via electrostatic-elastodynamic coupling - Schlögl, Tristan; Leyendecker, Sigrid; Reitelshöfer, Sebastian; Landgraf, Maximilian; Yoo, In Seong; Franke, Jörg (Proceedings of the IMSD, 2014)
The aim of this work is to set up a numerical framework to characterise the deformation process and effective forces when voltage is applied to dielectric elastomer actuators (DEA). As with capacitors, when an external voltage is applied to the conductive layers, an electric field is established. Resulting Maxwell stresses lead to a contraction of the DEA. These effects are described by the Maxwell equations, the balance of momentum and constitutive material laws. Based on a model for non-linear electro-elasticity that covers the static case only, inertia terms are included in order to obtain a description of the deformation process depending on time. A potential energy function that is composed of Neo-Hooke material behaviour, electric field energy and coupling terms covers the material behaviour. Combined with the kinetic energy, a Lagrange function forms the basis in a variational setting of the model. Approximating the action integral using quadrature rules, discretising with finite elements in space and finite differences in time and applying a discrete version of Hamilton’s principle [9], a structure preserving integration scheme for DEAs is obtained and evaluated
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.ltd.onmode

Optimization Problems in Production and Planning: Approaches and Limitations in View of Possible Quantum Superiority - Zwingel, Maximilian; May, Christopher; Reitelshöfer, Sebastian; Mauerer, Wolfgang (Annals of Scientific Society for Assembly, Handling and Industrial Robotics 2023, 2025)
Modern production and process planning is characterized by complex and diffuse interrelationships of parameters, properties and control values. New materials, innovative production technologies, differing degrees of automatability and application dependency form a multidimensional problem space for optimization, which cannot be efficiently solved by today’s technologies. Approximations in form of genetic algorithms, different heuristics and simplifications exist, but lack applicability due to high runtime and estimation errors. Quantum computers, quantum annealers and hybrid algorithms show potential to offer added value and better performance over established approaches for optimization, planning and production control, but are often incomprehensible for production engineers. Based on an analysis of industrial problems in different domains and a definition of relevant problem cases, the potential of quantum systems for optimization in production and planning is explored. An approach to close the gap between classical and quantum optimization from an engineering standpoint is made by describing the transformation process for a real-world problem and discussing performance indicators of model implementation
Keywords: Production planning; Optimization; Quantum algorithms

Path Detection with Artificial Neural Networks for the Navigation of Visually Impaired Jogger - Seßner, Julian; Lauer-Schmaltz, Martin; Reitelshöfer, Sebastian; Franke, Jörg (Dritte Transdisziplinäre Konferenz "Technische Unterstützungssysteme, die die Menschen wirklich wollen", 2018)

Pinch Valve Approach for a Biofilm Resistant Mechatronic Intraurethral Artificial Urinary Sphincter* - Preis, Alexander; Grigull, Ronja-Celine; Wang, Yacheng; Benke, Elisabeth; Martin, Sina; Rieker, Ralf; Franke, Jörg; Reitelshöfer, Sebastian (2023 45th Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2023)
Stress urinary incontinence is the involuntary leakage of urine during increased abdominal pressure, such as coughing, sneezing, laughing, or exercising. It can have a significant negative impact on a person's quality of life and can result in decreased physical activity and social isolation. The presented closure mechanism for a mechatronic intraurethral artificial urinary sphincter is designed to be inserted minimally invasive into the urethra. The device consists of a solid shell, which serves as a housing for the electronics and is designed to enable fixation in the urethra. During micturition, the urine flows through the system, where it is guided through an elastic silicone-tube that, on the one hand, enables closure by a squeezing mechanism and, on the other hand, prevents biofilm growth by oscillation at a frequency of 22.5 Hz. The squeezing mechanism consists of a pinch valve system actuated by a piezo motor. The system has been tested under urodynamic conditions and the results show that it is able to close the urethra effectively to restore continence. The device is able to withstand sudden loads and shows good performance in terms of biofilm prevention during first experiments with artificial urine. The results show that the mechatronic intraurethral artificial urinary sphincter has the potential to be an effective and minimally invasive alternative to current treatment options for stress urinary incontinence.Clinical Relevance— This novel concept of a mechatronic intraurethral artificial urinary sphincter presents a promising alternative treatment option for patients suffering from stress urinary incontinence. As it is designed to be inserted minimally invasive, it reduces the impact and complications associated with current treatment options. The future development and testing of the device could lead to a safe and effective option for clinicians to offer their patients with stress urinary incontinence, which can improve their quality of life, and decrease costs for society and healthcare systems.<br

PrIcosa: High-Precision 3D Camera Calibration with Non-Overlapping Field of Views - Kedilioglu, Oguz; Nova, Tasnim; Landesberger, Martin; Wang , Lijiu; Hofmann, Michael; Franke, Jörg; Reitelshöfer, Sebastian (Proceedings of the 20th International Joint Conference on Computer Vision, Imaging and Computer Graphics Theory and Applications - Volume 2 VISAPP: VISAPP, 2025)
Multi-camera systems are being used more and more frequently, from autonomous mobile robots to intelligent visual servoing cells. Determining the pose of the cameras to each other very accurately is essential for many applications. However, choosing the most suitable calibration object geometry and utilizing it as effectively as possible still remains challenging. Disadvantageous geometries provide only subpar datasets, increasing the need for a larger dataset and decreasing the accuracy of the calibration results. Moreover, an unrefined calibration method can lead to worse accuracies even with a good dataset. Here, we introduce a probabilistic method to increase the accuracy of 3D camera calibration. Furthermore, we analyze the effects of the calibration object geometry on the data properties and the resulting calibration accuracy for the geometries cube and icosahedron. The source code for this project is available at GitHub (Nova, 2024
Keywords: 3D Camera Calibration; Non-Overlapping Field of Views; Icosahedron; Probabilistic

Printed stretchable dielectric sensor grids for pressure monitoring in orthopedics - Martin, Sina; Gugel, Lukas; Schedel, Sophie; Reitelshöfer, Sebastian; Franke, Jörg (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
Scoliosis is a spinal deformity that can be treated with a scoliosis brace that applies pressure to the trunk. The child's body adapts to the applied pressure and the spine is corrected. However, the braces are adjusted periodically or after rapid growth without monitoring the adaptation process. This study proposes to investigate the pressure distribution in the internal padding of the brace in order to adapt the orthosis to the individual needs of the patient in the long term. For this purpose, the implementation of dielectric elastomer sensors is used to detect pressure peaks and valleys on a mutual capacitance sensing grid. Subsequently, direct ink writing is used to print electrode lines, allowing analysis of the flexible electrode grid geometries. The electrodes are characterized and tested under uniaxial strain. Furthermore, by placing the electrodes on the padding of the orthosis, the relative pressure distribution can be assessed. Our results demonstrate the application of dielectric elastomer sensors in orthopedics and explore the effect of different printed geometries. Although absolute values have not been evaluated, characterization of relative pressure differences is sufficient to detect pressure points. By monitoring long-term changes, therapy can be tailored to the body's individual adaptation process.
CRIS-Team Scopus Importer:2024-06-07
Keywords: additive manufacturing; Mutual capacitance; orthopedics; percolation; pressure sensor

Qualification of dielectric elastomer actuators as artificial muscles for highly dynamical N-DOF robot kinematics - Reitelshöfer, Sebastian; Landgraf, Maximilian; Franke, Jörg; Leyendecker, Sigrid (Proceedings of the 6th International Symposium on Adaptive Motion of Animals and Machines, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.ltd.qualif

Qualifizierung Dielektrischer-Elastomer-Aktoren zum Einsatz als künstliche Muskeln in hochdynamischen N-DOF Roboterkinematiken - Reitelshöfer, Sebastian; Landgraf, Maximilian; Franke, Jörg; Leyendecker, Sigrid (6. Bremer Bionik Kongress - Tagungsbeiträge, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.ltd.qualif

Qualifying dielectric elastomer actuators for usage in complex and compliant robot kinematics - Reitelshöfer, Sebastian; Landgraf, Maximilian; Schlögl, Tristan; Franke, Jörg; Leyendecker, Sigrid (EuroEAP, 2013)

Qualifying dielectric elastomer actuators for usage in complex and compliant robot kinematics - Reitelshöfer, Sebastian; Landgraf, Maximilian; Schlögl, Tristan; Franke, Jörg; Leyendecker, Sigrid (3rd international conference on Electromechanically Active Polymer (EAP) transducers & artificial muscles (EuroEAP), 2013)

Reachability analysis for cooperative processing with industrial robots - Wagner, Maximilian; Heß, Peter; Reitelshöfer, Sebastian; Franke, Jörg (IEEE International Conference on Emerging Technologies and Factory Automation, ETFA, 2017)
The cooperation of several industrial robots can improve processes or even makes new processes possible. In the scope of this work, the effect of the cooperation on the reachable workspace is investigated. Thus, the approach of reachability maps is extended to cooperative processing by simultaneously moving the tool and the workpiece. This allows a general statement about the improvement of the workpiece related reachability due to the simultaneous movement of tool and workpiece. A dual arm robot setup is used for implementation and the cooperative movement is compared to single arm movement by generating reachability maps for each case. In doing so, it is also presented how the integration of a collision detection improves the representativeness of the reachability maps.
CRIS-Team Scopus Importer:2023-03-07

Recognition and Description of Unknown Everyday Objects by Using an Image Based Meta-Search Engine for Service Robots - Reitelshöfer, Sebastian; Meister, Sebastian; Franke, Jörg (Advanced Engineering Forum Vol. 19, 2016)
In future applications service robots will operate in complex and unstructured environments. While performing daily tasks such systems will have to recognize many different unknown objects in order to be able to conduct continuative processes. To support enhanced functionalities of a service robot system an image based meta-search engine that is accessible for a machine can be used. In this contribution the realization of an approach to determine reasonable identification results for single and multiple everyday objects by using the Google reverse image search system is described. In order to deliver convenient results for the communication of a robotic system with a human user the generated search results are post-processed and prepared in order to provide reasonable object descriptions. To enable an intuitive application, control a gesture based approach allows potential users to initialize a search procedure by pointing at an object of interest while being observed by a camera system. The performed experiments show a quite reliable detection behavior for a reasonably broad variety of everyday objects.
Keywords: Object Recognition; Service Robot; Meta-Search Engine; Robot Operating System (ROS)

Robot-based Sample Tube Handling for Automated Pre- and Post-processing of SARS-CoV-2 PCR Tests - Seßner, Julian; Reitelshöfer, Sebastian; Lieret, Markus; Springs, Konstantin; Franke, Jörg (54th International Symposium on Robotics, ISR Europe 2022, 2022)
The SARS-CoV-2 pandemic worldwide has led to millions of infections with partly severe complications and death. The diagnosis is based on a PCR test of a saliva sample and is carried out in specialised laboratories. While the actual PCR analysis is usually automated, sample preparation and post-processing often involve manual handling steps. The paper presents an approach for robot-based pre- and post-processing of sample tubes. A seven-axis industrial robot is equipped with a multifunctional gripper and enabled for the application. In addition, machine-learning based image processing solutions are be integrated to increase flexibility and robustness. The implementation shows the feasibility of the approach in principle. The achieved cycle time does not fulfil the set requirements completely, but the implementation provides numerous approaches for optimisation.
CRIS-Team Scopus Importer:2022-09-16

Robotergestützte Sortierung radioaktiver Abfälle zwecks volumenoptimierter Konditionierung - VIRERO - Havenith, Andreas; Dürr, Martin; Helmes, Christopher; Krycki, Kai; Hansmann, Tim; Hansmann, Bengt; Reisenhofer, Florian; Simons, Frederic; Wangnick, Martina; Kohn, Sebastian; Querfurth, Frank; Sommer, Oliver; et al. (15th International Symposium “Conditioning of Radioactive Operational & Decommissioning Wastes” including 15th Status Report of BMBF “Decommissioning and Dismantling of Nuclear Facilities“, 2021)
Seit dem 01. Januar 2020 dürfen kernkraftwerksbetreibende Unternehmen (EVU), gemäß dem Gesetz zur Neuordnung der Verantwortung in der kerntechnischen Entsorgung, vernachlässigbar wärmeentwickelnde Abfälle an die BGZ Gesellschaft für Zwischenlagerung mbH übergeben, sofern diese fachgerecht verpackt sind. Bis zur geplanten Inbetriebnahme des Endlagers Konrad obliegt die Verantwortung für die Zwischenlagerung der BGZ. Der „Planfeststellungsbeschluss für die Errichtung und den Betrieb des Bergwerkes Konrad in Salzgitter“ vom 22. Mai 2002 sieht ein einlagerbares Abfallvolumen von 303.300 m³ vernachlässigbar wärmeentwickelnder radioaktiver Abfälle vor. Durch das begrenzte verfügbare Volumen des Endlagers ist eine Volumenoptimierung der endzulagernden Abfälle durch die EVUs als Verursacher wirtschaftlich attraktiv. In dem Projekt VIRERO (VIrtual REmote RObotics for Radiometric Sorting, 10/2020 – 09/2023) wird eine solche Volumenoptimierung durch eine teleoperierte Zerlegung und Neusortierung radioaktiver Abfälle mit hohen Ortsdosisleistungswerten (ODL-Werten) entwickelt und erprobt. Durch Zerlegung und Neusortierung lassen sich insbesondere hochradioaktive Abfallstücke (Hotspots) vom restlichen Abfall absondern, wodurch eine volumenoptimierte Verpackung des Abfalls erwirkt werden kann. Die Zerlegung und Sortierung des Abfalls erfolgt mittels innovativer Robotertechnik, welche mittels immersiver Augmented Reality und Virtual Reality Verfahren (AR/VR) gesteuert wird. Hierdurch entfällt die Handhabung durch mechanische Fernmanipulatoren. Die Separation der Hotspots und die Sortierung basiert auf einer Vielzahl von ortsaufgelösten Dosisleistungsmessungen oder ortsaufgelösten gammaspektrometrischen Messungen und einer hierauf aufbauenden Aktivitätsrekonstruktion aller Abfallteile. Diese Aktivitätsrekonstruktion wird durch die Kopplung von innovativer Kernstrahlungsmesstechnik mit industriell bewährter Laserscan-Technik erreicht.<br
Keywords: Decommissioning; Radioactive Waste Conditioning; Teleoperation; Virtual Reality; Augmented Virtuality

Roboter werden biomechatronische Assistenten - Reitelshöfer, Sebastian; Merz, Nina; Blank, Andreas; Kedilioglu, Oguz; Martin, Sina; Seßner, Julian; Franke, Jörg (2021)
Keywords: Biomechatronik; Human-Centered Robotics

Robust Obstacle Mapping for Visually Impaired Jogger on Less Structured Paths - Seßner, Julian; Ramer, Christina; Manert, Moritz; Reitelshöfer, Sebastian; Franke, Jörg (2019 IEEE/SICE International Symposium on System Integration, 2019)
This paper presents robust mapping of obstacles for an assistive system for blind and visually impaired jogger. The missing visual perception is substituted with a 3D stereo camera, capturing color and depth information from the environment. It is integrated into a lightweight backpack together with a single board computer. This paper focusses on the obstacle detection and mapping using the v-disparity method. To enhance the robustness of the mapping algorithm a roll angle detection and compensation is implemented. The algorithms are evaluated in different environments and proved their feasibility. The framerate is sufficient to detect obstacles in tim

Self-calibration method for a robotic based 3D scanning system - Wagner, Maximilian; Heß, Peter; Reitelshöfer, Sebastian; Franke, Jörg (2015 IEEE 20th Conference on Emerging Technologies Factory Automation (ETFA), 2015)
This paper describes a method for extrinsic sensor calibration for a 2D laser profile sensor on a robot arm used as a robot based 3D scanning system. In order to establish a relationship between the sensor measurements and the robot positions, the transformation between the robot flange and the sensor reference frame are determined. The developed calibration method is implemented as an automated self-calibration. It is based on the use of a pin as a fixed reference. The robot is aligned to the tip of the pin automatically with certain orientations. The sensor transformation is calculated based on six recorded robot positions. Finally, the accuracy of the calibration is determined with an additional robot position.
Keywords: calibration; manipulators; optical scanners; self-adjusting systems; 2D laser profile sensor; automated self-calibration; extrinsic sensor calibration; robot arm; robot flange; robotic based 3D scanning system; self-calibration method; sensor measurements; sensor reference frame; sensor transformation; Accuracy; Calibration; Robot kinematics; Robot sensing systems; Solid modeling; Three-dimensional displays

Sensor-guided jogging for visually impaired - Ramer, Christina; Ziegler, Christian; Reitelshöfer, Sebastian; Franke, Jörg (5th IEEE RAS/EMBS International Conference on Biomedical Robotics and Biomechatronics, 2014)
This paper introduces an approach for enabling visually impaired and blind people to practice jogging activities by 3D environment perception for course detection and collision avoidance, as well as feedback generation in an intuitive manner. Besides a system concept, first prototypic realizations, that confirm the general feasibility, are presented for this domain, which has not been addressed by research until now.
Keywords: handicapped aids; object detection; optical sensors; 3D environment perception; blind people; collision avoidance; course detection; feedback generation; optical sensors; sensor-guided jogging; visually impaired people; Belts; Cameras; Navigation; Sensors; Standards; Three-dimensional displays; Visualization

Soft Jamming Gripper with the External Prominence of Membrane for Human-Robot Cooperation - Shahsevani, Rasool; Reitelshöfer, Sebastian; Alimardani, Reza; Franke, Jörg (2019 IEEE 7TH INTERNATIONAL CONFERENCE ON CONTROL, MECHATRONICS AND AUTOMATION (ICCMA 2019), 2019)
CRIS-Team WoS Importer:2020-07-17

Soft Robotics mit DEA: Künstliche Muskeln für Roboterkollegen - Yoo, In Seong; Landgraf, Maximilian; Reitelshöfer, Sebastian; Franke, Jörg (Handling, 2015)

Stretchable, multi-modal sensors for vital data monitoring and healthcare applications - Martin, Sina; Reitelshöfer, Sebastian; Franke, Jörg (2021)
Keywords: flexible electronics; flexible sensors; silicones; soft sensors; healthcare; vital data monitoring; printed electronics

Tensegrity-Inspired Joint Can Protect from Impacts by Isolating - Walter, Jonas; Rothfischer, Lukas; Stierstorfer, Richard; Nemoto, Takeru; Franke, Jörg; Reitelshöfer, Sebastian (Mechanisms and Machine Science, 2023)
Cable-driven parallel robots are known for their highly dynamic motions. At the same time, tensegrity robots are considered to be robust due to their intrinsic compliance. In a previous work, it was shown that a cable-driven joint with a tensegrity-inspired design allows fast rotations. The question remains whether such a joint is not only fast, but could also protect its base link from impacts due to its special design. In this paper, it is shown that a tensegrity-inspired joint can protect from impacts by isolating. A hardware prototype of such a joint was loaded with a modal hammer. It was found that the joint isolates impact forces up to 83%, demonstrating its ability to effectively absorb and dissipate energy from external impacts. Putting the results in a more general context, such a joint, however, can be used not only (a) passively to protect a base link, but also (b) actively for high-speed motions of a follower link by pulling a lightweight mass with parallel attached and actuated cables. It is anticipated that this study could be a starting point for the creation of novel robotic kinematics, composed of conventional and tensegrity kinematics, to build fast and robust robots.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Cable-Driven Joint; Impact Protection; Tensegrity

Towards Adaptive Environment Perception and Understanding for Autonomous Mobile Robots - Hofmann, Christian; Taliercio, Franca; Walter, Jonas; Franke, Jörg; Reitelshöfer, Sebastian (2023 IEEE Symposium Sensor Data Fusion and International Conference on Multisensor Fusion and Integration (SDF-MFI), 2023)
Autonomous mobile robots (AMRs) are increasingly used in various applications like intralogistics, hospitality and agriculture. Though, their software and abilities are still mainly designed and implemented for specific environments and tasks, impeding an even more widespread deployment of AMRs. Their environment perception and understanding lacks automated adaption to specific operating environments and conditions.In this paper, we propose a software architecture that allows the automated adaption of AMRs’ environment perception and understanding to different operating environments. Further, we provide a concise review of state-of-the-art approaches and technologies needed. We present an exemplary implementation and evaluate the proposed architecture. On this basis, advantages and open research questions of the architecture are derived.<br
Keywords: Software architecture; Semantics; Data integration; Computer architecture; Robot sensing systems; Software; Agriculture; Mobile Robot; Adaptive Perception; Semantic Environment Representation

Towards a Synthetic Tissue Model of the Lower Urinary Tract - Preis, Alexander; Merkl, Christina; Miralles, Paula; Heer, Svenja; Benke, Elisabeth; Reitelshöfer, Sebastian; Martin, Sina; Rieker, Ralf; Franke, Jörg (Proceedings of the 16th International Joint Conference on Biomedical Engineering Systems and Technologies BIOSTEC - (Volume 1), 2023)
The development of medical devices often depends on in vivo studies to validate the proper functioning of the products. These trials provide ethical as well as economic challenges, which can be partially addressed by the usage of realistic synthetic tissue models that replicate human anatomy and the corresponding properties of the biological tissue. In this work, a silicone-based model with a fiber structure and a PVA-based model that exhibits fabrication-induced anisotropy are presented in the special context of the lower urinary tract. The analysis of the materials in the uniaxial tensile test shows the anisotropic and viscoelastic properties of the materials. Furthermore, the anatomical model of the lower urinary tract shows expected deformation in simulation as well as in the real silicone model. Additionally, a suitable artificial urine according to ISO 20696 is shown for use with the model. First experiments to change the pH of the artificial urine are successfully conducted.<br
Keywords: Anatomical Model; Urology; Lower Urinary Tract; Urinary Bladder; Urethra; Artificial Urine

Towards Imaginative Robots: A Generative Pipeline for Simulated Environments - May, Christopher; Suchy, Lorenz; Franke, Jörg; Reitelshöfer, Sebastian (Langbeiträge ASIM SST, 2024)
Autonomous Mobile Systems (AMS) offer significant advantages in industry and private sectors by adapting to diverse and dynamic environments. To train these systems, large amounts of data are required, typically obtained from simulated environments. However, the creation of these environments is often labor-intensive. Here, we propose a generative pipeline that provides a streamlined approach to virtual training and testing while allowing users to apply automated methods including generative AI. Our pipeline consists of four, partly iterative main steps. The pipeline spans from the creation of individual assets to the utilization of the simulated environments. The pipeline is then implemented for an exemplary scenario, utilizing multiple methods including generative AI. Furthermore, we propose a novel application of our pipeline to provide robots with the capabilities to “imagine” virtual experiences. The presented pipeline not only simplifies the process of generating simulated environments, but also resembles a scalable framework for developing increasingly complex AMS. <br

Towards Useful Social Capabilities for Robots in Healthcare - Merz, Nina; Wittenberg, Thomas; Klein, Stina; Lu, Shuang; Zebisch, Raoul; Retzer, Lukas; Niessen, Cornelia; Kraus, Matthias; Andre, Elisabeth; Lang-Richter, Nadine; Pest, Christian; Berger, Julia; et al. (2024 2nd International Conference on Integrated Systems in Medical Technologies (ISMT), 2024)
Social robots aim to solve existing challenges in healthcare and nursing. Nevertheless, such robots are not yet capable of robustly engaging in a diverse range of social interactions. Furthermore, the development of such robots and their adaptation to new healthcare scenarios is both time-consuming and cost intensive. Resulting in only pilot studies in some exemplary healthcare scenarios. This contribution presents the Concept for Enabling Robots for Useful Social Interactions in Healthcare (CERUSI-Health) - including requirements, software architecture, social situative communication and socially adaptive and proactive interaction for social robots and simulation and validation and impacts of social robots. The objective of CERUSI-Health is to overcome existing obstacles to the use of social robots as assistants in the healthcare and nursing sector. The concept is based on the current state of research and thus including open research gaps, but provides guidance on how these can be addressed. Given the variety of tasks in the healthcare and nursing sector, it is possible to enable different kinds of robots to act socially by following CERUSI-Healt

Weiterentwicklung dielektrischer Elastomeraktoren zu Antriebselementen nachgiebiger Robotersysteme - Reitelshöfer, Sebastian; Landgraf, Maximilian; Franke, Jörg (Internationales Forum Mechatronik 2013, 2013)